Knowledge, perception and behavior about food consumption related to the prevention of Opisthorchiasis among people in upper northeastern Thailand in 2013 - วิริยะวิภาต, ชื่นพันธ์; แถวโนนงิ้ว, เกษร; กลางบุรัมย์, วันทนา (Disease Control Journal, 2015)
Opisthorchis Viverrini (OV) or Liver fluke is one of major public health problem for many countries in Southeast Asia, including upper northeastern region of Thailand as well. The main cause of the disease is due to eating raw fishes of uncooked fish product. This study was a cross-section survey with the main objectives to study knowledge, perception and behavior at risk of OV infection and relating factors that enabling appropriate change of risk behavior of people in the upper northeastern region of Thailand. The population study were 3,915 people of >15 years who were randomized by thirty cluster survey from the population of seven provinces of the upper northeastern region. Research instrument was questionnaire. De¬scriptive and inferential statistics were employed in data analysis. The research result showed that forty one point two percent of them did not know the appropriate cooking to kill the causative agent, while fifty five point two percent did not know the risk of eating raw fish towards the diseases. They, however, perceived clearly that eating raw fish was their own life style which was inherited from their ancestors who were familiarized and very fond of food cooking from raw fish. That was why fifty seven point one percent of them were still eating raw fish and ninety two point six percent liked eating raw fermented foods. Meanwhile, it was found that fifty two percent of them never thought to change their risk behavior. In regard to factors related to modification of such risk behavior, sex, risk meal eating behavior, education, occupation and family history of liver cancer and cancer of bile duct were statistically significant factors with 0.05 confidence interval (p-value 0.001, 0.002, 0.003, 0.004 and 0.034) respectively. These important factors, there¬fore were necessary to explain their willingness and commitment to modify their eating behavior. Authors concluded that, in order to achieve better interventions for modification of risk behaviors of upper northeastern people, more continuously effective education and behavior modification must be delivered to them with a very strong political and local commitments and supports.